(untitled) (Maneggio, 2025)
In order to increase the economic needs of the South Tambun community in managing waste bank management by conducting outreach to the community, especially members of the waste bank forum, in order to get business partners or investors through attractive presentations using the Canva Magic Presentation method.The purpose of implementing community service (PkM) is to provide development of the competencies possessed by the community, improve skills in presenting material to the community and members of the waste bank, improve expertise and carry out activities to support the waste bank business and its management for increasing the income and economy of the community and members of the waste bank forum as an effort to strengthen membership participation and empower its members, groups and communities for the welfare of its members which has an impact on increasingWelfare and business economic development as outputs from the implementation of Community Service Program (PKM) at the South Tambun Waste Bank Forum. The solution to addressing the competency gap between the objectives of the waste bank forum is throughconducting socialization and training on effective communication techniques, providing material on business communication for community participation and getting potential investors, providing material on business communication for community participation and getting potential investors, and being able to explain material on how to make effective presentations using the Canva Magic Presentation method